MEMS-micropumps : a review - Huang, Xiaoyang (2012)
Microfluidics has emerged from the MEMS-technology as an important research field and a promising market. This paper gives an overview on one of the most important microfluidic components: the micropump. In the last decade, various micropumps have been developed. There are only a few review papers on microfluidic devices and none of them were dedicated only to micropumps. This review paper outlines systematically the pump principles and their realization with MEMS-technology. Comparisons regarding pump size, flow rate, and backpressure will help readers to decide their proper design before starting a microfluidics project. Different pump principles are compared graphically and discussed in terms of their advantages and disadvantages for particular applications.